Relationship Between Characteristics of Class 3 Inspired Patients With Service Satisfaction at Mokopido General Hospital, Tolitoli Regency - Novi Inriyanny Suwendro; Bertin Ayu Wandira; Putri Maharani (Media Publikasi Cendekia Indonesia, 2022)
Patient satisfaction is a measure of service quality in hospitals. Satisfaction can be influenced by various aspects, one of which is patient characteristics. The purpose of the study was to analyze the relationship between the Characteristics of Class 3 Inpatients and Service Satisfaction at Mokopido General Hospital, Baolan, Tolitoli Regency. This type of quantitative research with a Cross-Sectional approach. The population in this study amounted to 1,178 patients; a sample of 93 patients was obtained using the slovin formula, while sampling was using the Proportionate Stratified Random Sampling technique. The analysis used was the Contingency Correlation with a value of =10%. The results of this study indicated a strong relationship between patient characteristics in the form of last education (p = 0.000) and age (p = 0.000) with service satisfaction. There is a strong relationship between age group, education and service satisfaction at Mokopido General Hospital, Baolan, Tolitoli Regency. Older respondents are more satisfied with their services. Respondents who are not educated are more satisfied with the services received. Suggestions for the empathy dimension are expected that the doctor or nurse will be able to be polite, and friendly, listen to complaints about the patient's illness, and provide a way out in the consultation so that the patient is satisfied with the service